Incentive Preferences and Its Related Factors Among Primary Medical Staff in Anhui Province, China: A Cross-Sectional Study - Sang, Lingzhi; Liu, Hongzhang; Yan, Huosheng; Rong, Jian; Cheng, Jing; Wang, Li; Li, Guoqiang; Guo, Yan; Zhang, Lei; Ding, Hong; Chen, Guimei; Chen, Ren (Frontiers in Public Health, 2022)
Background The shortage of primary medical staff is a major problem in the management of health human resources across many developing countries. By determining their preferences for various motivational and related factors, we examined the correlation between staff’s motivation preference levels and staff turnover and turnover intention. This study aimed to further improve the incentive mechanism and to provide a reference for healthcare managers to formulate management strategies for the primary medical staff team. Methods A self-reported questionnaire survey was conducted to collect data. The basic survey content included demographic characteristics. The absolute level questionnaire and relative level questionnaire on the factors affecting motivation preference were used as the main assessment scales. A total of 1,112 primary health workers in Anhui Province were investigated. T-test, analysis of variance (ANOVA), exploratory factor analysis, and multiple linear regression analysis were performed to analyze the data. Results The survey respondents (45.1%) reported being satisfied with their relationship with colleagues, and other social relationships (46.9 %). The Kaiser Meyer Olkin (KMO) value for the absolute preference degree for motivational factors was 0.951. Two factors (economic and non- economic factors), after using the maximum variance rotation axis method, explained 81.25% of the total variance. The regression analysis showed that primary medical staff members with low monthly income(B=-0.157) have a higher preference for non-economic factors; the higher the educational background(B=0.133), the higher their preference for economic factors. In addition, with the increase in participants’ age(B=-0.250), the preference for motivational factors gradually decreased. Conclusion Both economic and non-economic factors play an important role in enhancing the enthusiasm of primary medical workers and improving their work attitude. Managers should use their influence to stabilize the primary medical staff.